2005
DOI: 10.1111/j.1469-8137.2005.01349.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the generality of global leaf trait relationships

Abstract: Summary• Global-scale quantification of relationships between plant traits gives insight into the evolution of the world's vegetation, and is crucial for parameterizing vegetationclimate models.• A database was compiled, comprising data for hundreds to thousands of species for the core 'leaf economics' traits leaf lifespan, leaf mass per area, photosynthetic capacity, dark respiration, and leaf nitrogen and phosphorus concentrations, as well as leaf potassium, photosynthetic N-use efficiency (PNUE), and leaf N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
642
11
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 2,389 publications
(709 citation statements)
references
References 66 publications
51
642
11
5
Order By: Relevance
“…Previous studies on trade-offs among leaf traits concentrated mainly on traits related to carbon assimilation, leaf structure or chemical concentrations [45,46,56,57]. Leaf carbon traits of tropical rainforest seedlings studied here were in agreement with general trade-offs since carbon assimilation increases with increasing N and SLA, and decreases with increasing C and LD (Tab.…”
Section: Association Of Traitssupporting
confidence: 70%
“…Previous studies on trade-offs among leaf traits concentrated mainly on traits related to carbon assimilation, leaf structure or chemical concentrations [45,46,56,57]. Leaf carbon traits of tropical rainforest seedlings studied here were in agreement with general trade-offs since carbon assimilation increases with increasing N and SLA, and decreases with increasing C and LD (Tab.…”
Section: Association Of Traitssupporting
confidence: 70%
“…Menge and Field (2007) found that N fertilization led to P limitation in six out of eleven previously N-limited ecosystems, mainly because N input could accelerate P cycling rates across a wide variety of terrestrial ecosystems (Marklein and Houlton, 2012). Nevertheless, most investigations on P fertilization have been conducted in N-rich Yavitt et al, 2011;Santiago et al, 2012;Mori et al, 2013) or P-limited conditions (De Groot et al, 2003;Wright et al, 2005), while only few studies have investigated how P fertilization influences productivity in N-limited ecosystems (Blevins et al, 2006;Carlson et al, 2014;Gotore et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, V cmax provides a measure of photosynthetic capacity that can be readily incorporated into canopy process models. Maximum leaf photosynthesis rates (A max ) are generally related to leaf N concentrations (Field and Mooney, 1986), although the relationship between the two can vary among taxa and among regions (Wright et al, 2005). Establishing global relationships between photosynthetic parameters like V cmax and A max and more easily measured leaf traits like N concentration and leaf mass per area (LMA) offers a promising avenue toward parameterization of global biogeochemical models (Reich et al, 2007).…”
Section: Introductionmentioning
confidence: 99%